Ex Vivo Blockade of the PD-1 Pathway Improves Recall IFNγ Responses of HIV-Infected Persons on Antiretroviral Therapy - Fischhaber, Natalie; Schmiedeberg, Moritz; Kübel, Sabrina; Harrer, Ellen; Harrer, Thomas; Nganou-Makamdop, Krystelle (Vaccines, 2023)
Despite antiretroviral therapy (ART), immune exhaustion persists in HIV infection and limits T cell responses to HIV or other pathogens. Moreover, HIV infection results in the loss of pre-existing immunity. Here, we investigated the effect of blocking the PD-1 pathway on recall IFNγ responses to tetanus toxoid (TT) and measles virus (MV) antigens in HIV-infected persons on ART with prior TT and MV immunity. The ex vivo treatment of lymphocytes with anti-PD-1 and anti-PD-L1 antibodies significantly increased TT- and MV-specific IFNγ responses. The responses to TT and MV antigens alone or in combination with antibodies blocking the PD-1 pathway positively correlated with CD4 T cell levels. Furthermore, T cell PD-1 expression levels inversely correlated with recall IFNγ responses in combination with antibodies blocking the PD-1 pathway but not with IFNγ responses to antigens only. Our study suggested that targeting the PD-1 pathway may boost vaccine-induced pre-existing immunity in HIV-infected persons on ART depending on the degree of immune exhaustion.
CRIS-Team Scopus Importer:2023-03-17
Keywords: anti-PD-1; anti-PD-L1; HIV infection; PD-1 pathway; T cell exhaustion; vaccine-induced immunity